Deciding Who Gets to Decide - Gabel, Susan (Disability Studies Quarterly, 2006)
On the surface, Rosen's study would appear to be the story of the successful advocacy for Deaf culture and language in schools. In this response, I read the subtext of Rosen's article, in which troubling questions arise about systemic structures that work against full access to decision making, the dilemma of diversity, the problem of participatory parity for disabled students who have been shut out of the democratic process, and the question of who gets to decide which arguments about education prevail.